Indicator reducing motions - Chandler, Howard McCune (My University, 1903)
Blueprints for Indicator Reducing Motion, No. 1 for air compressor at K.S.A.C. Eng. Lab, and Indicator Reducing Motion, No. 2 for Corliss Engine at Manhattan Milling Company's Mill.
Citation: Chandler, Howard McCune. Indicator reducing motions. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Blueprints; Indicator reducing motion devices; Theses